Change in urban land use and associated attributes in the Upper San Francisco Estuary, 1990-2006 - Stoms, D. M. (San Francisco Estuarine & Watershed Science, 2010)
Land use is an ultimate driver of many of the stressors on the Upper San Francisco Estuary, but the magnitude and pattern of land use change has not been analyzed. I attempted to fill this knowledge gap through a screening-level risk assessment. I compared urban land use within hydrodynamic subregions in 1990, 2000, and 2006. Ancillary data were then used to quantify secondary measures such as impervious cover, housing density, road density and road crossings. Despite the rapid growth of the Bay Area, Sacramento, and Stockton metropolitan areas, the percentage of urban area and rates of change in the subregions are generally low to moderate when compared to other estuaries in the United States. The spatial data sets used in this analysis have been posted online to a public repository to be used by other researchers addressing topics such as fate and transport of contaminants.
Keywords: urban growth geographic information systems GIS hydrodynamic subregions housing density road-stream crossings impervious cover